2011
DOI: 10.1002/term.410
|View full text |Cite
|
Sign up to set email alerts
|

Vascularization of prevascularized and non-prevascularized fibrin-based human adipose tissue constructs after implantation in nude mice

Abstract: Adipose regeneration strategies have been hampered by the inability to supply an adequate vascular supply following implantation. Vascularization in vitro, also called prevascularization, is a promising method that could promote the vascularization of engineered adipose tissue constructs upon implantation. In this study we compared the ability of prevascularized-to-non-prevascularized fibrin-based human adipose tissue to promote vascularization. Human adipose tissue-derived stromal cells (ASCs) and different m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Such strategies include the provision of various proangiogenic factors, 21,22 genetic modification of cells to overproduce growth factors, 23,24 specific biomaterial design to mimic the extracellular matrix with high porosities, 25 and embedding ECs into engineered tissue constructs. 26,27 However, the time required for EC migration, angiogenic sprouting, and vasculogenesis is still too long to guarantee the viability of bioengineered tissue after implantation and for it to merge and fuse with host tissue. 28 It has been reported that extensive networks are formed at day 5 when engineered replacements are prevascularized with HUVEC before implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Such strategies include the provision of various proangiogenic factors, 21,22 genetic modification of cells to overproduce growth factors, 23,24 specific biomaterial design to mimic the extracellular matrix with high porosities, 25 and embedding ECs into engineered tissue constructs. 26,27 However, the time required for EC migration, angiogenic sprouting, and vasculogenesis is still too long to guarantee the viability of bioengineered tissue after implantation and for it to merge and fuse with host tissue. 28 It has been reported that extensive networks are formed at day 5 when engineered replacements are prevascularized with HUVEC before implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our in vitro data in similar hydrogels, [25] we had hypothesized that the development of robust vasculature would require the presence of both exogenous endothelial and perivascular cell sources; however, in similar subcutaneous mouse studies, vascularization was not significantly different between fibrin-based constructs seeded with MSC/HUVEC co-cultures compared to those seeded with MSC only. [18] Recent insight in to the secretome of AFSCs may help explain these results. Paracrine factors produced by AFSCs, including vascular endothelial growth factor, stromal cell-derived factor 1, interleukin 8, and monocyte chemotactic protein 1, were isolated and shown to be capable of enhancing vasculogenesis in a murine model.…”
Section: Discussionmentioning
confidence: 99%
“…[10,12,15] While some studies have shown that seeding endothelial cells into tissue constructs before implantation may improve in vivo perfusion and cell viability, [1,16,17] others have shown no difference between the rate of in vivo blood vessel formation in hydrogels pre-vascularized with endothelial cells in vitro compared to mesenchymal stem cell (MSC)-seeded hydrogels relying on in situ vascularization alone. [18] Studies have also shown that combining both endothelial cells and a perivascular cell source, such as MSCs or fibroblasts, is essential in the generation of robust functional vascular networks in vivo. [19][20][21] F o r P e e r R e v i e w 4 One potential source of both endothelial and perivascular cell types is amniotic fluidderived stem cells (AFSC).…”
mentioning
confidence: 99%
“…Examples of endpoints include the time to blood perfusion of the implant with host circulation after implantation, changes in endothelial-cell-specific marker expression, total vessel length per unit area (e.g., centimeters per square centimeter) based on bright field microscopy or endothelial cell surface antibody staining (e.g., anti-human CD31), vessel density per unit crosssection area (e.g., vessel per square centimeter) after histology staining, and even evidence of new collagen synthesis in the implant [20][21][22].…”
Section: Introductionmentioning
confidence: 99%